A tale of two rice varieties: Modelling the prehistoric dispersals of japonica and proto-indica rices. (November 2018) - Silva, Fabio; Weisskopf, Alison; Castillo, Cristina; Murphy, Charlene; Kingwell-Banham, Eleanor; Qin, Ling; Fuller, Dorian Q
We model the prehistoric dispersals of two rice varieties, japonica and proto- indica, across Asia using empirical evidence drawn from an archaeobotanical dataset of 400 sites from mainland East, Southeast and South Asia. The approach is based on regression modelling wherein goodness of fit is obtained from log–log quantile regressions of the archaeologically inferred age versus a least-cost distance from the origin(s) of dispersal. The Fast Marching method is used to estimate the least-cost distances based on simple geographical features. We explicitly test three hypotheses for the arrival of japonica rice to India where, it has been proposed, it hybridized with the indigenous proto- indica, subsequently spreading again throughout India. Model selection, based on information criteria, highlights the role of the Inner Asia Mountain Corridor in introducing japonica rice into northeast India, followed closely by a 'mixed-route' model, where japonica was also almost simultaneously introduced via Assam, Bangladesh and Myanmar. Finally, we estimate the impact of future archaeological work on model selection, further strengthening the importance of the Inner Asia Mountain Corridor.